The regional neuronal activity in left posterior middle temporal gyrus is correlated with the severity of chronic aphasia - Li J (Dove Medical Press, 2017)
Jianlin Li,1,* Dunren Du,2,* Wei Gao,1 Xichun Sun,3 Haizhu Xie,1 Gang Zhang,1 Jian Li,1 Honglun Li,1 Kefeng Li4 1Department of Radiology, Yantai Yuhuangding Hospital, 2Department of Radiology, Yantai Laishan Branch Hospital of Yuhuangding Hospital, Medical College of Qingdao University, 3Department of Radiology, Yantai Hospital of Traditional Chinese Medicine, Yantai, China; 4School of Medicine, University of California, San Diego, CA, USA *These authors contributed equally to this work Background: Aphasia is one of the most disabling cognitive deficits affecting >2 million people in the USA. The neuroimaging characteristics of chronic aphasic patients (>6 months post onset) remain largely unknown.Objective: The objective of this study was to investigate the regional signal changes of spontaneous neuronal activity of brain and the inter-regional connectivity in chronic aphasia. Materials and methods: Resting-state blood oxygenation level-dependent functional magnetic resonance imaging (fMRI) was used to obtain fMRI data from 17 chronic aphasic patients and 20 healthy control subjects in a Siemens Verio 3.0T MR Scanner. The amplitude of low-frequency fluctuation (ALFF) was determined, which directly reflects the regional neuronal activity. The functional connectivity (FC) of fMRI was assessed using a seed voxel linear correlation approach. The severity of aphasia was evaluated by aphasia quotient (AQ) scores obtained from Western Aphasia Battery test.Results: Compared with normal subjects, aphasic patients showed decreased ALFF values in the regions of left posterior middle temporal gyrus (PMTG), left medial prefrontal gyrus, and right cerebellum. The ALFF values in left PMTG showed strong positive correlation with the AQ score (coefficient r=0.79, P<0.05). There was a positive FC in chronic aphasia between left PMTG and left inferior temporal gyrus (BA20), fusiform gyrus (BA37), and inferior frontal gyrus (BA47\45\44). Conclusion: Left PMTG might play an important role in language dysfunction of chronic aphasia, and ALFF value might be a promising indicator to evaluate the severity of aphasia. Keywords: aphasia, severity, ALFF, correlation, functional connectivity, aphasia quotient